2022
DOI: 10.1186/s12864-022-08324-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of TALE superfamily in Triticum aestivum reveals TaKNOX11-A is involved in abiotic stress response

Abstract: Background Three-amino-loop-extension (TALE) superfamily genes are widely present in plants and function directly in plant growth and development and abiotic stress response. Although TALE genes have been studied in many plant species, members of the TALE family have not been identified in wheat. Results In this study, we identified 70 wheat TALE protein candidate genes divided into two subfamilies, KNOX (KNOTTED-like homeodomain) and BEL1-like (BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…The cation proton antiporter (CPA) superfamily, including K + efflux antiporter (KEA) and cation/H + exchanger (CHX) family proteins as well as the Na + /H + exchanger (NHX), TaNHX4-B.1, and TaNHX4-B.4, facilitated differential drought, salt, and heat stress tolerance to Escherichia coli [64]. A similar phenomenon occurs with transcription factors, in which orthologous or paralogue genes that are produced via gene duplication exhibit identical or opposite expression patterns when subjected to abiotic stress, including NAC [71][72][73][74], DREB [75], Hsf [76][77][78][79], MYB [80,81], bZIP [82,83], WRKY [84,85], AP2/ERF [86], GRF [87], and the homeobox genes HD-Zip [88], TALE [89,90], ZF-HD [91], and WOX [92,93]. Taking TaTAIL as an example, Rathour et al systemically identified and analyzed TAIL family members in wheat, including gene and protein structural properties, phylogeny, and expression patterns.…”
Section: Diversity and Divergence Of Duplicate Genes Involved In Abio...mentioning
confidence: 80%
See 1 more Smart Citation
“…The cation proton antiporter (CPA) superfamily, including K + efflux antiporter (KEA) and cation/H + exchanger (CHX) family proteins as well as the Na + /H + exchanger (NHX), TaNHX4-B.1, and TaNHX4-B.4, facilitated differential drought, salt, and heat stress tolerance to Escherichia coli [64]. A similar phenomenon occurs with transcription factors, in which orthologous or paralogue genes that are produced via gene duplication exhibit identical or opposite expression patterns when subjected to abiotic stress, including NAC [71][72][73][74], DREB [75], Hsf [76][77][78][79], MYB [80,81], bZIP [82,83], WRKY [84,85], AP2/ERF [86], GRF [87], and the homeobox genes HD-Zip [88], TALE [89,90], ZF-HD [91], and WOX [92,93]. Taking TaTAIL as an example, Rathour et al systemically identified and analyzed TAIL family members in wheat, including gene and protein structural properties, phylogeny, and expression patterns.…”
Section: Diversity and Divergence Of Duplicate Genes Involved In Abio...mentioning
confidence: 80%
“…In addition to the above cases, a list of duplicate genes is provided in Table 1, including homologous and paralogous genes with structural and functional differences that contribute to wheat response to abiotic stress. A few such examples include drought-responsive TaHVA1, TaRAV, and TaNAC [72,73,160,161]; salt-responsive TaCHYR, TaWRKY75, and TaKNOX11 [84,90,129]; cold-responsive TaEXPA, TaICE, and TaAREB [108,162,163]; and heat-responsive TaMYB, TabZIP, and TaHAG [80,82,83,164,165]. Histone demethylase drought stress [190] TaSIRFP-3A,TaSIRFP-3B RING-HC-type E3 ligases cold stress [191] Plants 2023, 12, 2465 9 of 21…”
Section: Contribution Of Duplicate Genes To Abiotic Stress Resistancementioning
confidence: 99%
“…We built an unrooted phylogenetic tree to investigate the evolutionary relationships of the proteins encoded by the 21 genes. In contrast to earlier research, we categorized these proteins into seven distinct groups [ 29 , 30 ]. The KNOX genes are categorized into two groups, whereas the BELL genes are further classified into five groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Required barley TALE CDs and genomic DNA sequences were downloaded from the Ensembl Plants database. TALE protein sequences of T. aestivum , G. max , and P. trichocarpa were obtained from published papers ( Zhao et al., 2019 ; Wang et al., 2021 ; Han et al., 2022 ). Arabidopsis protein sequences were obtained from TAIR ( https://www.arabidopsis.org/ ), while TALE protein sequences of Oryza sativa and Zea mays were obtained from PlantTFDB v4.0 ( http://planttfdb.gao-lab.org/ ) ( Jin et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…At present, genome-wide analysis of the TALE family has been completed in many plants such as Arabidopsis thaliana ( Hamant and Pautot, 2010 ), Populus trichocarpa ( Zhao et al., 2019 ), Glycine max ( Wang et al., 2021 ), and Triticum aestivum ( Han et al., 2022 ). Meanwhile, considering the importance of this family in the development of flowers and leaves in the Poaceae family, it is urgent and necessary to conduct research on the barley TALE gene family.…”
Section: Introductionmentioning
confidence: 99%